Design and development of temperature and humidity control system using PID and Labview on a 20 kV cubicle - Imelda Uli Vistalina simanjuntak; Agung Yoke Basuki; Lukman Medriavin; Muhammad Yusuf (VOLT : Jurnal Ilmiah Pendidikan Teknik Elektro, 2022)
Damage to the 20 kV cubicle at PLN Branch Lahat often occurs because the overheater causes considerable losses. Insulation failure at the corroded cubicle terminal results in a decrease in heat production and heater resistance. So there is a mall function (saturated) and a short circuit. Therefore, this study aims to design a prototype to maintain temperature and humidity conditions in a 20 kV cell using Proportional Integral Derivatives (PID) and LabVIEW. Set the Kp, Kd, and Ki parameters, namely proportional, derivative, and integral constants, so that the desired temperature can be maintained to prevent corrosion. The parameter value was obtained at the set point of 40 °C by a value of Kp is 1, Ki is 0.1, and Kd is 0.05, resulting in a rise time of 188 s, a peak time of 216 s, stabilization of 288 s, and a steady-state error of 0.30%. In addition, the setpoint is 43°C, the rise time is 272 s, the peak time is 311 s, the settling time is 377 s, and the steady-state error is 0.60%. Moreover, the 45°C setpoint has a rise time of 338 s, a peak time of 380 s, a settling time of 448 s, and a steady-state error of 0.93%. These results indicate a reasonably good prototype performance.